MCR synthesis of a tetracyclic tetrazole scaffold. Issue 11 (1st June 2015) - Patil, Pravin; Khoury, Kareem; Herdtweck, Eberhardt; Dömling, Alexander
Graphical abstract: Abstract: Scaffold diversity is key in the ongoing exercise of discovery of novel bioactive compounds using high throughput screening (HTS). Based on the Ugi tetrazole synthesis we have designed novel bi- and tri-cyclic scaffolds featuring interesting pharmacophore properties. The compounds of the scaffold (B ) are synthesizable in large diversity and numbers in two steps using (hetero)phenylethylamines, HN3, oxo components and iscyanoacetaldehyde(dimethylacetale). The chemistry is amenable to parallel synthesis and is used to enhance and fill the screening decks of the European Lead factory (ELF). Here, we are reporting full experimental details, scope and limitations of the reaction, cheminformatic analysis and the 3D structures of selected compounds.